Investigation of the High-Voltage Converter for Powering Electrostatic Precipitators - Roginskaya Lyubov; Yalalova Zulfiya; Gorbunov Anton; Karimov Ruslan; Tereshkin Vladimir; Senyushkin Nikolai (E3S Web of Conferences, 2023)
The article is devoted to the study of the power supply for air purification systems using electrostatic precipitators (ESP). The features of operation of the in-put thyristor regulator for changing the output parameters of the power source are considered. The nominal electromagnetic and design parameters of the elements of the ESP power supply circuit are presented. Mathematical expressions describing electromagnetic processes in the ESP are given. A computer simulation of a system including a power supply with an ESP was performed, taking in-to account the real parameters of the device elements. The characteristics of out-put parameters of the power supply are obtained for various firing angles of the input regulator and various connected numbers of turns of the high-voltage trans-former.